1996
DOI: 10.1037/0033-2909.120.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization–habituation may occur during operant conditioning.

Abstract: Operant response rates often change within experimental sessions, sometimes increasing and then decreasing. The authors attribute these changes to sensitization and habituation to aspects of the experimental situation presented repeatedly (e.g., reinforcers) or for a prolonged time (e.g., the experimental enclosure). They describe several empirical similarities between sensitization-habituation and within-session changes in operant responding. They argue that many alternative explanations for within-session ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
163
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(174 citation statements)
references
References 99 publications
(209 reference statements)
10
163
1
Order By: Relevance
“…Additional arguments may be found in McSweeney and Roll (1998) and McSweeney and Murphy (2000). In addition, McSweeney, Hinson, and Cannon (1996) argued that within-session changes in responding for food share at least 11 of the 14 characteristics of behavior undergoing habituation (see asterisks in Table 1). Although the results of any one study might be dismissed, attributing within-session changes in responding to satiation becomes less tenable as the data and formal arguments in favor of habituation accumulate.…”
Section: Separating Satiation and Habituationmentioning
confidence: 98%
See 1 more Smart Citation
“…Additional arguments may be found in McSweeney and Roll (1998) and McSweeney and Murphy (2000). In addition, McSweeney, Hinson, and Cannon (1996) argued that within-session changes in responding for food share at least 11 of the 14 characteristics of behavior undergoing habituation (see asterisks in Table 1). Although the results of any one study might be dismissed, attributing within-session changes in responding to satiation becomes less tenable as the data and formal arguments in favor of habituation accumulate.…”
Section: Separating Satiation and Habituationmentioning
confidence: 98%
“…We have already presented evidence that habituation contributes to the loss of reinforcer effectiveness when food, an ingestive stimulus, serves as the reinforcer (for summaries, see McSweeney, Hinson, & Cannon, 1996;McSweeney & Murphy, 2000;McSweeney & Roll, 1998 of behavior undergoing habituation: spontaneous recovery (Table 1, Characteristic 1), dishabituation (Table 1, Characteristic 4), and stimulus specificity (Table 1, Characteristic 2). To illustrate, Figure 5 presents evidence of dishabituation.…”
Section: Separating Satiation and Habituationmentioning
confidence: 99%
“…Not all infants who are exposed briefly to contingent stimulation will exceed baseline levels of responding, nor will any increase in responding that is due to sensitization or arousal unrelated to contingency learning be sustained. Mean learning data obscure such within-session response variability during learning (McSweeny, Hinson, & Cannon, 1996). Infants who exceeded the criterion were considered to have responded to the contingency appropriately; infants who were below the criterion were considered to have not responded appropriately.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…With respect to the current study, one of these variables is more general while the other may be specific to wheel running. McSweeney and colleagues (McSweeney, Hinson, & Cannon, 1996;McSweeney & Murphy, 2009) have shown that response rates vary within sessions, showing patterns of increasing rates, decreasing rates, or rates that increase and then decrease. Habituation to the sensory aspects of reinforcement leads response rates to decrease, whereas sensitization does the opposite.…”
mentioning
confidence: 99%